(untitled) (Estudos Japoneses, 2019)
The article presents a summary of a thesis about other possible interpretations and perspectives on development processes from oral reports on the history of the Nikkei community from Paracatu-MG, composed of people and groups that migrated to the Municipality in the second half of the 20th century, in the context of the opening of new agricultural frontiers in Cerrado, provided by programs such as PRODECER. An understanding of development processes as experiences that emerge from subjectivities in their diversity and complexity, grouped in the dimensions of migration, work, education, community and culture, was achieved through the application of concepts and approaches from the post-colonial studies in the analysis of the Nikkei’s development aspirations, values and expectations throughout their life trajectories.